Curcuma lithophila and C. rufostriata (Zingiberaceae), two new species from Thailand, and additional notes on C. papilionacea - Soonthornkalump, Sutthinut; Pungpairote, Tidarat; Niwesrat, Sira; Leong-Skornickova, Jana (Thai Forest Bulletin (Botany), 2021)
Curcuma lithophila and C. rufostriata, two new species from Curcuma subgen. Hitcheniopsis, are described and illustrated. They are compared with their morphologically closest species, Curcuma rhabdota, C. papilionacea and C. sparganiifolia. Notes on distribution, ecology, etymology, uses and IUCN provisional assessments are provided. Further notes on the distribution of the recently described C. papilionacea and an improved IUCN conservation assessment are reported from additional collections.